Optimizing Public Services in Islamic Education: A Multi-Site Study on PTSP Management Strategies in Madrasahs - Mohammad Haris Jamroni; Saihan Saihan; Mashudi Mashudi (JURNAL AL-TANZIM, 2026)
This study aims to analyze the management strategies of the One-Stop Integrated Service (PTSP) in optimizing administrative quality within Madrasahs. Employing a qualitative multi-site case study approach, the research utilized in-depth interviews, observation, and document analysis; data were analyzed using the interactive model developed by Miles, Huberman, and Saldaña and verified through source and technique triangulation. The findings reveal that Madrasah Tsanawiyah employs an "adaptive human-touch" strategy prioritizing interpersonal relationships and flexibility, whereas Madrasah Aliyah implements a "structured system-driven" strategy emphasizing standardization and digitalization. Both strategies effectively enhance administrative quality within their respective user contexts, though they still require strengthening in areas where each faces limitations. The study concludes that the success of PTSP depends on an institution's responsiveness to user characteristics rather than on system uniformity. These findings offer theoretical implications by reinforcing the contingency approach in public service management and provide practical implications for the Ministry of Religious Affairs and Madrasahs in designing adaptive service policies grounded in the values of amanah, ihsan, and itqan.